Revisiting a Hypothesis: Tracing Early Buddhist Heritage in Central-Eastern Europe - Puskas Khetani, Katalin (Technium Social Sciences Journal, 2021)
The following paper is a revisitation of a hypothesized cultural connection between the Szekler gates, predominantly from Transylvania (in the Carpathian Basin), and the Sacred gate tradition found across Asia. The structure of this paper is built upon three different approaches: firstly, the recent publications and historical records on this topic; secondly the ethnographical similarities in function and symbolism between the Szekler gates and the gateways found across Asia; and thirdly the observable similarities and analogies between the ornaments and symbols used on Szekler gates and other Asian gateway structures are examined. This article aims to investigate if the observable analogies and similarities are just the result of a strange coincidence, or if there is indeed a cultural connection between the Szekler gate and the similar constructions across Asia as hypothesized by several 19th and early 20th-century researchers of the topic.